DNA methylation in APOE: The relationship with Alzheimer's and with cardiovascular health. Issue 1 (27th April 2020) - Mur, Jure; McCartney, Daniel L.; Walker, Rosie M.; Campbell, Archie; Bermingham, Mairead L.; Morris, Stewart W.; Porteous, David J.; McIntosh, Andrew M.; Deary, Ian J.; Evans, Kathryn L.; Marioni, Riccardo E.
Abstract: Introduction: Genetic variation in the apolipoprotein E ( APOE ) gene is associated with Alzheimer's disease (AD) and risk factors for cardiovascular disease (CVD). DNA methylationat APOE has been associated with altered cognition and AD. It is unclear if epigenetic marks could be used for predicting future disease. Methods: We assessed blood‐based DNA methylation at 13 CpGs in the APOE gene in 5828 participants from the Generation Scotland (GS) cohort. Using linear mixed models regression, we examined the relationships among APOE methylation, cognition, cholesterol, the family history of AD and the risk for CVD. Results: DNA methylation at two CpGs was associated with the ratio of total cholesterol and HDL cholesterol, but not with cognition, family history of AD, or the risk of CVD. Discussion: APOE methylation is associated with the levels of blood cholesterol, but there is no evidence for the utility of APOE methylation as a biomarker for predicting AD or CVD.